2021
DOI: 10.1002/ls.1572
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plasma nitriding pre‐treatment on the corrosion and tribocorrosion behaviours of PVD CrN, TiN and AlTiN coated AISI 4140 steel in seawater

Abstract: CrN, TiN and AlTiN coatings were applied by the Physical Vapour Deposition (PVD) method on AISI 4140 and plasma nitrided (PN) AISI 4140 steel. The study aimed to investigate the effect of plasma nitriding before PVD on the corrosion and tribocorrosion behaviour of AISI 4140 steel in seawater. The electrochemical corrosion behaviour of the samples was evaluated in natural seawater by the potentiodynamic polarisation method. Tribocorrosion tests were performed against alumina in natural seawater under 5 N load a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…As a result of pitting and cracks, Cl − ions can pass through the surface film due to their small size. 15,18,21,28,29…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of pitting and cracks, Cl − ions can pass through the surface film due to their small size. 15,18,21,28,29…”
Section: Resultsmentioning
confidence: 99%
“…As a result of pitting and cracks, Cl − ions can pass through the surface film due to their small size. 15,18,21,28,29 It can be seen in Figure 2 that the curves shift to more cathodic potentials and higher corrosion currents under sliding tribocorrosion conditions. Also, fluctuations in the curves can be observed in tribocorrosion conditions due to the continuous breakdown and regeneration of the passive film.…”
Section: Cyclic Potentiodynamic Polarization With and Without Slidingmentioning
confidence: 96%
“…Although boron aluminide coating does not show an utterly passive behaviour in seawater like stainless steel, the formation of pits outside the trace instead of inside the track may be evidence that the coating layer exhibits a passivelike behaviour Alkan, 2022a). In this case, the worn region under the effect of sliding may have exhibited anodic behaviour, while the unworn regions may have performed cathodic behaviour Alkan and Gök, 2022). 10.…”
Section: Assessment Of Ocp During Corrosion and Tribocorrosionmentioning
confidence: 99%
“…Siddiqui et al [ 11 ] reported a 53% improvement in the adhesion strength of CrN coatings deposited on duplex-treated tool steel. Alkan et al [ 21 ] described that plasma nitriding before coating significantly improves corrosion and tribo-corrosion resistance of PVD CrN, TiN, and AlTiN coatings.…”
Section: Introductionmentioning
confidence: 99%